Zjawisko ikiryō jako przykład podróży dusz w japońskiej literaturze dworskiej (VIII-XII wiek) - Pączkowska, Agnieszka (Studia Azjatystyczne, 2015)
According to ancient Japanese beliefs invisible ghosts could freely travel between the worlds of supernatural and human. However, the travel was not limited to the souls of dead. It was believed that a soul could leave the body of a living person, do mischief and return. Such occurrence was called ikiryō. This paper analyses examples of such phenomenon depicted in two literary sources: Lady Rokujō from Murasaki Shikibu’s (978? 1016?) Genji monogatari (1008) and an unnamed noblewoman from Konjaku monogatarishū (1120). In both instances emotions play great role in creating ikiryō. Women’s souls separate from the body and serve punishment for sufferings caused by unfaithful men. However, there is a distinct difference in the matter of one’s awareness in becoming ikiryō. Lady Rokujō is unaware of her soul’s travels and experiences them as traumatic episodes of psychosis. On the other hand the unnamed noblewoman willingly turns her soul into ikiryō to deliver vengeance on her ex-lover and regains peace afterwards. Ikiryō is a manifestation of one’s true emotions. It shows not only the complexity of Japanese concept of a soul but also touches on the issue of women social status during Heian period.